Lanthanum-antimony-rare earth added copper-zinc alloy and preparation method thereof

By adding lanthanum and antimony to the copper-zinc alloy and using zinc-rare earth intermediate alloy, the problem of dezincification of copper-zinc alloy in special environments is solved, and its anti-dezincification performance and corrosion resistance are significantly improved.

CN119433281AActive Publication Date: 2025-02-14鹤山市金益铜业有限公司
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411567698.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-02-14
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

Copper-zinc alloys are prone to dezincification under seawater corrosion and high temperature environments, resulting in degradation of material performance and even failure, limiting its application range and increasing maintenance costs.

Method used

By adding lanthanum and antimony to the copper, the structure of the copper is improved, and the alloy structure is refined to reduce the pore size of zinc atoms between the primary cells and the grain boundary, and the antimony forms an oxide film to prevent dezincification corrosion. In addition, zinc-rare earth intermediate alloys are added to improve the compatibility and rare earth properties of lanthanum and antimony.

Benefits of technology

It significantly improves the anti-dezincification performance of copper-zinc alloy, reduces the occurrence of dezincification, and improves the mechanical properties and corrosion resistance of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a lanthanum-antimony-rare earth added copper-zinc alloy and a preparation method thereof, and relates to the technical field of rare earth alloys, the copper-zinc alloy comprises the following substances by mass fraction: 63.2-65.7% of electrolytic copper, 32.4-34.9% of a zinc-rare earth intermediate alloy and 1.3-1.8% of an alloy additive; the zinc-rare earth intermediate alloy comprises zinc, lanthanum, antimony, silicate and a carbon source; the mass ratio of the zinc to the lanthanum to the antimony to the silicate to the carbon source is 34 to (0.05 to 0.15) to (0.03 to 0.09) to (0.27 to 0.34) to (0.16 to 0.21). The dezincification resistance of the alloy added with the lanthanum and the antimony is remarkably improved. Other elements are added into the alloy, the mixing degree exists, a zinc-rare earth intermediate alloy is prepared by adding silicate and a carbon source, the zinc-rare earth intermediate alloy is added into electrolytic copper in an intermediate alloy mode, the compatibility of lanthanum and antimony in copper can be effectively improved, and the performance of rare earth is fully played.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of rare earth alloys, and in particular to a lanthanum-antimony-rare earth-added copper-zinc alloy and a preparation method thereof. Background Art

[0002] As an important industrial material, copper-zinc alloy is widely used in electrical, mechanical, construction and other fields. Traditional copper-zinc alloy is favored for its excellent mechanical properties and good processing performance, but in some special application environments, such as seawater corrosion and high temperature environment, copper-zinc alloy is prone to dezincification, resulting in material performance degradation or even failure. This problem not only limits the application scope of copper-zinc alloy, but also increases maintenance costs and affects product reliability and life.

[0003] The invention patent publication number CN118256775A discloses a copper alloy and its preparation method and application. The copper alloy includes the following components in percentage by weight: Cu: 59.0-61.5wt%, Te: 0.005-0.015wt%, P: 0.01-0.02wt%, As: 0.005-0.01wt%, Si<0.001wt%, Al<0.001wt%, Sn<0.001wt%, Mg<0.001wt%, Fe<0.005wt%, Pb<0.005wt%, Zn balance; the proportion of β phase in the copper alloy is less than 10%. The present invention adopts hot rolling + online β / α phase transformation heat treatment to significantly reduce the proportion of β phase in the alloy, so that the prepared copper alloy has excellent anti-dezincification performance, good processing plasticity and bendability, and does not lose copper powder at a high-speed stamping of 800-1200m / min. However, dezincification occurs not only in the β phase but also in the α phase. Reducing the proportion of the β phase alone cannot effectively reduce the occurrence of dezincification, which results in the alloy's poor anti-dezincification performance. Summary of the invention

[0004] The purpose of the present application is to provide a lanthanum, antimony and rare earth added copper-zinc alloy to solve the problem of anti-dezincification in the copper-zinc alloy.

[0005] In the first aspect, the present application provides a lanthanum, antimony and rare earth added copper-zinc alloy adopts the following technical solution: A lanthanum, antimony and rare earth added copper-zinc alloy, based on the total weight of the copper-zinc alloy, the copper-zinc alloy includes the following substances in mass fraction: Electrolytic copper 63.2-65.7%, zinc-rare earth master alloy 32.4-34.9% and alloy additives 1.3-1.8%; The zinc-rare earth master alloy comprises zinc, lanthanum, antimony, silicate and a carbon source; The mass ratio of zinc, lanthanum, antimony, silicate and carbon source is 34: (0.05-0.15): (0.03-0.09): (0.27-0.34): (0.16-0.21).

[0006] By adopting the above technical solution, adding lanthanum and antimony to copper can effectively improve the organizational morphology of copper. Lanthanum can refine the alloy structure. On the one hand, it reduces the number of primary cells in the organization and reduces the dezincification phenomenon caused by electrochemical corrosion. On the other hand, refining the alloy structure can reduce the detachment of zinc atoms between grain boundaries, reduce the dezincification rate, and thus alleviate the dezincification phenomenon. Antimony can form an oxide film and occupy the detachment site after the zinc atoms fall off, thereby preventing the further occurrence of dezincification corrosion. The dezincification resistance of the alloy after the addition of lanthanum and antimony is significantly improved. Adding other elements to the alloy has problems such as the degree of mixing. By adding silicates and carbon sources to make zinc-rare earth intermediate alloys, and adding them to electrolytic copper in the form of intermediate alloys, the compatibility of lanthanum and antimony in copper can be effectively improved, and the performance of rare earth can be fully utilized.

[0007] Optionally, the method for preparing the zinc-rare earth master alloy comprises the following steps: S001, zinc, lanthanum and antimony are mixed and melted in two portions; S002, adding silicate to a portion of the melt to obtain a first melt, S003, adding a carbon source to another portion of the melt to obtain a second melt; S004. Casting the first melt and the second melt in the mold in sequence to obtain a zinc-rare earth master alloy.

[0008] By adopting the above technical solution, at high temperature, silicate will react with carbon source to generate silicon element and generate gases such as carbon monoxide. Therefore, it is necessary to divide the intermediate alloy into two parts for preparation and cast them in sequence so that the carbon source and silicate in the zinc-rare earth intermediate alloy can be in a separated state. When the zinc-rare earth intermediate alloy is added to the copper alloy, at high temperature, after the zinc-rare earth intermediate alloy is melted, the carbon source with a higher melting point reacts with silicate, thereby introducing trace silicon elements and generating gases, which is beneficial to improving the fluidity of the molten alloy, making the rare earth elements more evenly dispersed, and giving full play to the performance of the rare earth elements.

[0009] Optionally, the silicate is selected from one or more of zinc silicate and aluminum silicate, and the carbon source is selected from one or more of graphene and carbon nanotubes.

[0010] By adopting the above technical solution, zinc silicate and aluminum silicate can produce zinc and aluminum elements after the reaction, avoiding the introduction of new impurities. Graphene and carbon nanotubes are porous carbon single-substance structures with high melting points and chemical stability, and can maintain stable performance during the preparation of zinc-rare earth master alloys.

[0011] Optionally, in step S002, the melting temperature is between 670-750°C, in step S003, the melting temperature is between 580-640°C, and the melting operation is performed under an inert atmosphere.

[0012] By adopting the above technical solution, since the main component of the zinc-rare earth master alloy is zinc, the temperature for preparing the master alloy does not need to be too high, and the main body of the master alloy can be molten. In the molten state, a small amount of substances can also be evenly dispersed in the master alloy. In order to avoid oxidation of the carbon source, the mixing of the carbon source needs to be carried out in an inert atmosphere.

[0013] Optionally, in step S004, the zinc-rare earth master alloy is cast into a volume between 40 cm 3 -80cm 3 Spherical.

[0014] By adopting the above technical solution, the spherical alloy with a small volume can make the zinc-rare earth master alloy be added to the copper alloy in a dispersed state, which is convenient for the rapid and uniform dispersion of each element in the alloy.

[0015] Optionally, the alloy additives include aluminum, iron, phosphorus, tin, indium and zirconium.

[0016] By adopting the above technical solution, aluminum, iron, phosphorus, tin, indium and zirconium are added as alloy additives, which can significantly improve the mechanical properties and corrosion resistance of the alloy. Aluminum can enhance the strength and hardness of the alloy, iron helps to improve the wear resistance and heat resistance of the alloy, phosphorus can improve the fluidity and weldability of the alloy, tin can increase the ductility and toughness of the alloy, indium helps to refine the grains and improve the comprehensive mechanical properties of the alloy, and zirconium can effectively inhibit the adverse effects of impurity elements in the alloy, further improving the overall performance of the alloy.

[0017] In the second aspect, the present application provides a method for preparing a lanthanum antimony rare earth added copper-zinc alloy using the following technical solution: A method for preparing a lanthanum antimony rare earth added copper-zinc alloy, based on the above-mentioned lanthanum antimony rare earth added copper-zinc alloy, comprising the following steps: S011, melting electrolytic copper, and adding an alloy additive to the molten electrolytic copper to obtain an intermediate mixture; S012, adding zinc-rare earth master alloy to the intermediate mixture and continuing to stir until no bubbles are generated; S013. After slag removal, casting is performed in a mold to obtain a rare earth copper-zinc alloy.

[0018] By adopting the above technical solution, the spherical zinc-rare earth master alloy is dispersed and added into the intermediate mixture, so that the zinc-rare earth master alloy can be quickly dispersed into the intermediate mixture after being melted in the molten intermediate mixture. After the zinc-rare earth master alloy is added, the mixing of the elements can generate gas to promote the dispersion of the elements, so that the elements can fully play their role.

[0019] Optionally, in step S011, the melting temperature of the electrolytic copper is between 1050-1150° C., and in step S012, the mixing temperature is between 1000-1050° C., and the stirring rate is between 30-40 r / min.

[0020] By adopting the above technical solution, the melting temperature can ensure that each element is in a molten state, and some impurities with low melting points are vaporized, and impurities with high melting points are deposited, thereby refining a high-purity alloy. The lower stirring rate can avoid air stirring and ensure the stability of each alloy element.

[0021] In summary, the present application includes at least one of the following beneficial technical effects: 1. Adding lanthanum and antimony to copper can effectively improve the organizational morphology of copper. Lanthanum can refine the alloy structure. On the one hand, it reduces the number of primary cells in the structure and reduces the dezincification phenomenon caused by electrochemical corrosion. On the other hand, refining the alloy structure can reduce the detachment of zinc atoms between grain boundaries, reduce the dezincification rate, and thus alleviate the dezincification phenomenon. Antimony can form an oxide film and occupy the detachment site after the zinc atoms fall off, thereby preventing the further occurrence of dezincification corrosion. The dezincification resistance of the alloy after the addition of lanthanum and antimony is significantly improved. Adding other elements to the alloy has problems such as the degree of mixing. By adding silicates and carbon sources to make zinc-rare earth intermediate alloys, and adding them to electrolytic copper in the form of intermediate alloys, the compatibility of lanthanum and antimony in copper can be effectively improved, and the performance of rare earths can be fully utilized; 2. At high temperatures, silicates react with carbon sources to generate silicon and produce gases such as carbon monoxide. Therefore, it is necessary to prepare the master alloy in two parts and cast them in sequence so that the carbon source and silicates in the zinc-rare earth master alloy can be in a separated state. When the zinc-rare earth master alloy is added to the copper alloy, the zinc-rare earth master alloy is melted at high temperature, and the carbon source with a higher melting point reacts with the silicates, thereby introducing trace silicon elements and generating gases, which is beneficial to improving the fluidity of the molten alloy, making the rare earth elements more evenly dispersed, and giving full play to the performance of the rare earth elements; 3. By dispersing and adding spherical zinc-rare earth master alloys into the intermediate mixture, the zinc-rare earth master alloy can be quickly dispersed into the intermediate mixture after being melted in the molten intermediate mixture. After the zinc-rare earth master alloy is added, the mixing of various elements can generate gas to promote the dispersion of various elements, so that each element can fully play its role. DETAILED DESCRIPTION

[0022] The present application is further described in detail below in combination with embodiments and comparative examples.

[0023] In the following preparation examples, embodiments and comparative examples, the silicate selected is zinc silicate and the carbon source used is graphene.

[0024] Preparation Example 1 The preparation of zinc-rare earth master alloy comprises the following steps: S031. After 255 g of zinc is melted, the temperature is raised to 710°C, and stirring is maintained. 0.75 g of lanthanum, 0.45 g of antimony and 4.50 g of zinc silicate are added respectively, and the mixture is stirred at 45 r / min for 30 min to obtain the first melt.

[0025] S032. After 255 g of zinc was melted, the temperature was raised to 610°C, and stirring was continued. 0.75 g of lanthanum, 0.45 g of antimony and 2.77 g of graphene were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain a second melt.

[0026] S033, in volume 45cm 3 -50cm 3 The first melt is cast in the spherical mold at a pulling speed of 25 mm / s. After the first melt solidifies, the second melt is cast at a pulling speed of 25 mm / s. After the second melt solidifies, a zinc-rare earth master alloy is obtained.

[0027] Preparation Example 2 The preparation of zinc-rare earth master alloy comprises the following steps: S031. After 255 g of zinc was melted, the temperature was raised to 670°C, and stirring was continued. 0.38 g of lanthanum, 0.23 g of antimony and 4.05 g of zinc silicate were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain the first melt.

[0028] S032. After 255 g of zinc was melted, the temperature was raised to 580°C, and stirring was continued. 0.38 g of lanthanum, 0.23 g of antimony and 2.40 g of graphene were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain a second melt.

[0029] S033, in volume 45cm 3 -50cm 3The first melt is cast in the spherical mold at a pulling speed of 25 mm / s. After the first melt solidifies, the second melt is cast at a pulling speed of 25 mm / s. After the second melt solidifies, a zinc-rare earth master alloy is obtained.

[0030] Preparation Example 3 The preparation of zinc-rare earth master alloy comprises the following steps: S031. After 255 g of zinc was melted, the temperature was raised to 750°C, and stirring was continued. 1.13 g of lanthanum, 0.68 g of antimony and 5.10 g of zinc silicate were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain the first melt.

[0031] S032. After 255 g of zinc was melted, the temperature was raised to 640°C, and stirring was continued. 1.13 g of lanthanum, 0.68 g of antimony and 3.15 g of graphene were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain a second melt.

[0032] S033, in volume 45cm 3 -50cm 3 The first melt is cast in the spherical mold at a pulling speed of 25 mm / s. After the first melt solidifies, the second melt is cast at a pulling speed of 25 mm / s. After the second melt solidifies, a zinc-rare earth master alloy is obtained.

[0033] Preparation Example 4 The preparation of zinc-rare earth master alloy comprises the following steps: S031. After 255 g of zinc is melted, the temperature is raised to 710°C, and stirring is maintained. 0.75 g of lanthanum, 0.45 g of antimony and 4.05 g of zinc silicate are added respectively, and the mixture is stirred at 45 r / min for 30 min to obtain a first melt.

[0034] S032. After 255 g of zinc was melted, the temperature was raised to 610°C, and stirring was continued. 0.75 g of lanthanum, 0.45 g of antimony and 3.15 g of graphene were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain a second melt.

[0035] S033, in volume 45cm 3 -50cm 3 The first melt is cast in the spherical mold at a pulling speed of 25 mm / s. After the first melt solidifies, the second melt is cast at a pulling speed of 25 mm / s. After the second melt solidifies, a zinc-rare earth master alloy is obtained.

[0036] Preparation Example 5 The preparation of zinc-rare earth master alloy comprises the following steps: S031. After 255 g of zinc is melted, the temperature is raised to 710°C, and stirring is maintained. 0.75 g of lanthanum, 0.45 g of antimony and 5.10 g of zinc silicate are added respectively, and the mixture is stirred at 45 r / min for 30 min to obtain a first melt.

[0037] S032. After 255 g of zinc was melted, the temperature was raised to 610°C, and stirring was continued. 0.75 g of lanthanum, 0.45 g of antimony and 2.40 g of graphene were added respectively, and the mixture was stirred at 45 r / min for 30 min to obtain a second melt.

[0038] S033, in volume 45cm 3 -50cm 3 The first melt is cast in the spherical mold at a pulling speed of 25 mm / s. After the first melt solidifies, the second melt is cast at a pulling speed of 25 mm / s. After the second melt solidifies, a zinc-rare earth master alloy is obtained.

[0039] Example 1 The preparation of copper-zinc alloy comprises the following steps: S041. Melt 645.0 g of electrolytic copper, raise the temperature to 1100° C., add 6.0 g of lithium, 4.2 g of iron, 2.9 g of phosphorus, 2.4 g of tin, 1.5 g of indium and 1.8 g of zirconium, stir until mixed evenly, and obtain an intermediate mixture.

[0040] S042. Lower the temperature to 1050° C., add 336.2 g of the zinc-rare earth intermediate alloy prepared in Preparation Example 1 to the intermediate mixture prepared in step S041, and continue stirring at a stirring rate of 35 r / min until no bubbles are generated to obtain a molten alloy.

[0041] S043, raising the temperature to 1150° C., refining and deslagging the molten alloy prepared in step S042, and then draining the molten copper to a casting furnace with a temperature of 900-1000° C. and a casting speed of 260-280 rpm to obtain a copper-zinc alloy.

[0042] Example 2 The preparation of copper-zinc alloy comprises the following steps: S041. Melt 632.2 g of electrolytic copper, raise the temperature to 1100°C, add 6.0 g of lithium, 4.2 g of iron, 2.9 g of phosphorus, 2.4 g of tin, 1.5 g of indium and 1.8 g of zirconium, stir until mixed evenly, and obtain an intermediate mixture.

[0043] S042. Lower the temperature to 1050° C., add 349.0 g of the zinc-rare earth intermediate alloy prepared in Preparation Example 1 to the intermediate mixture prepared in step S041, and continue stirring at a stirring rate of 35 r / min until no bubbles are generated to obtain a molten alloy.

[0044] S043, raising the temperature to 1150° C., refining and deslagging the molten alloy prepared in step S042, and then draining the molten copper to a casting furnace with a temperature of 900-1000° C. and a casting speed of 260-280 rpm to obtain a copper-zinc alloy.

[0045] Example 3 The preparation of copper-zinc alloy comprises the following steps: S041. Melt 657.0 g of electrolytic copper, raise the temperature to 1100° C., add 6.0 g of lithium, 4.2 g of iron, 2.9 g of phosphorus, 2.4 g of tin, 1.5 g of indium and 1.8 g of zirconium, stir until mixed evenly, and obtain an intermediate mixture.

[0046] S042. Lower the temperature to 1050° C., add 324.2 g of the zinc-rare earth intermediate alloy prepared in Preparation Example 1 to the intermediate mixture prepared in step S041, and continue stirring at a stirring rate of 35 r / min until no bubbles are generated to obtain a molten alloy.

[0047] S043, raising the temperature to 1150° C., refining and deslagging the molten alloy prepared in step S042, and then draining the molten copper to a casting furnace with a temperature of 900-1000° C. and a casting speed of 260-280 rpm to obtain a copper-zinc alloy.

[0048] Example 4 The preparation of copper-zinc alloy comprises the following steps: S041. Melt 647.9 g of electrolytic copper, raise the temperature to 1100°C, add 4.5 g of lithium, 3.6 g of iron, 2.2 g of phosphorus, 1.5 g of tin, 0.9 g of indium and 0.6 g of zirconium, stir until mixed evenly, and obtain an intermediate mixture.

[0049] S042. Lower the temperature to 1050° C., add 339.8 g of the zinc-rare earth intermediate alloy prepared in Preparation Example 1 to the intermediate mixture prepared in step S041, and continue stirring at a stirring rate of 35 r / min until no bubbles are generated to obtain a molten alloy.

[0050] S043, raising the temperature to 1150° C., refining and deslagging the molten alloy prepared in step S042, and then draining the molten copper to a casting furnace with a temperature of 900-1000° C. and a casting speed of 260-280 rpm to obtain a copper-zinc alloy.

[0051] Example 5 The preparation of copper-zinc alloy comprises the following steps: S041. Melt 641.5 g of electrolytic copper, raise the temperature to 1100°C, add 6.5 g of lithium, 5.4 g of iron, 3.9 g of phosphorus, 3.4 g of tin, 3.0 g of indium and 2.8 g of zirconium, stir until mixed evenly, and obtain an intermediate mixture.

[0052] S042. Lower the temperature to 1050° C., add 333.5 g of the zinc-rare earth intermediate alloy prepared in Preparation Example 1 to the intermediate mixture prepared in step S041, and continue stirring at a stirring rate of 35 r / min until no bubbles are generated to obtain a molten alloy.

[0053] S043, raising the temperature to 1150° C., refining and deslagging the molten alloy prepared in step S042, and then draining the molten copper to a casting furnace with a temperature of 900-1000° C. and a casting speed of 260-280 rpm to obtain a copper-zinc alloy.

[0054] Example 6 The difference from Example 1 is that the zinc-rare earth master alloy prepared in Preparation Example 2 of equal mass is used to replace the zinc-rare earth master alloy prepared in Preparation Example 1.

[0055] Example 7 The difference from Example 1 is that the zinc-rare earth master alloy prepared in Preparation Example 3 of equal mass is used to replace the zinc-rare earth master alloy prepared in Preparation Example 1.

[0056] Example 8 The difference from Example 1 is that the zinc-rare earth master alloy prepared in Preparation Example 4 of equal mass is used to replace the zinc-rare earth master alloy prepared in Preparation Example 1.

[0057] Example 9 The difference from Example 1 is that the zinc-rare earth master alloy prepared in Preparation Example 5 of equal mass is used to replace the zinc-rare earth master alloy prepared in Preparation Example 1.

[0058] Comparative Example 1 The difference from Example 1 is that 335.6 g of zinc, 0.9 g of lanthanum and 0.5 g of antimony are used to replace 337 g of the zinc-rare earth master alloy.

[0059] The copper-zinc alloys prepared in the examples and comparative examples were subjected to performance tests.

[0060] Tensile strength: The tensile strength is measured in accordance with GB / T 228.1-2021 "Tensile Tests on Metallic Materials", Part 1: Room Temperature Test Methods, Articles 10 and 20.

[0061] Dezincification corrosion: Dezincification corrosion is carried out according to the national standard GB / T 10119 dezincification test requirements. The dezincification corrosion test is carried out in a constant temperature water bath at 75±0.5℃. The sample is placed in a 10g / L CuCl2 solution with a sample placement height of 15mm for 24 hours. After the dezincification test, the sample is cut vertically along the exposed surface, and the cut surface is used as the observation surface for grinding and polishing, and the dezincification corrosion is observed under a microscope.

[0062] Table 1 Performance test results of copper-zinc alloys prepared in the examples and comparative examples The properties of the copper-zinc alloy were investigated according to Table 1, Examples and Comparative Examples.

[0063] Compared with Examples 1-5, the difference lies in the different proportions of raw material components in the copper-zinc alloy. It can be seen that the copper-zinc alloys with different raw material component proportions have better tensile strength and shallower dezincification layer depth, indicating that the copper-zinc alloys prepared in Examples 1-5 have better anti-desizinization performance while having conventional alloy properties, can avoid zinc element precipitation during long-term use, and improve the durability of the copper-zinc alloy.

[0064] Comparing Examples 1 and 6-9, the difference is that the raw material component ratios of the zinc-rare earth master alloy are different. It can be seen that the zinc-rare earth master alloys prepared with different raw material component ratios have better tensile strength and shallower dezincification layer depth when the components of other raw materials are consistent, and have better anti-desizinization performance.

[0065] Comparing Example 1 with Comparative Example 1, the difference is that Comparative Example 1 uses a mixture of equal masses of zinc, lanthanum and antimony to replace the zinc-rare earth master alloy. It can be seen that compared with Example 1, the copper-zinc alloy prepared in Comparative Example 1 can maintain similar tensile strength, but the depth of the dezincification layer is deeper, indicating that more zinc elements are shed and the anti-dezincification performance is weaker, which further indicates that the addition of the zinc-rare earth master alloy is beneficial to improving the anti-dezincification performance of the copper-zinc alloy.

[0066] The embodiments of this specific implementation are all preferred embodiments of the present application, and are not intended to limit the protection scope of the present application. The same components are represented by the same symbols. Therefore, any equivalent changes made based on the structure, shape, and principle of the present application should be included in the protection scope of the present application.

Claims

1. A lanthanum, antimony and rare earth added copper-zinc alloy, characterized in that: Based on the total weight of the copper-zinc alloy, the copper-zinc alloy includes the following substances by mass fraction: Electrolytic copper 63.2-65.7%, zinc-rare earth master alloy 32.4-34.9% and alloy additives 1.3-2.5%; The zinc-rare earth master alloy comprises zinc, lanthanum, antimony, silicate and a carbon source; The mass ratio of zinc, lanthanum, antimony, silicate and carbon source is 34: (0.05-0.15): (0.03-0.09): (0.27-0.34): (0.16-0.21).

2. The lanthanum-antimony-rare earth-added copper-zinc alloy according to claim 1, characterized in that: The preparation method of the zinc-rare earth master alloy comprises the following steps: S001, zinc, lanthanum and antimony are mixed and melted in two portions; S002, adding silicate to a portion of the melt to obtain a first melt, S003, adding a carbon source to another portion of the melt to obtain a second melt; S004. Casting the first melt and the second melt in the mold in sequence to obtain a zinc-rare earth master alloy.

3. The lanthanum-antimony-rare earth added copper-zinc alloy according to claim 1, characterized in that: The silicate is selected from one or more of zinc silicate and aluminum silicate, and the carbon source is selected from one or more of graphene and carbon nanotubes.

4. The lanthanum-antimony-rare earth-added copper-zinc alloy according to claim 2, characterized in that: In the step S002, the melting temperature is between 670-750°C, and in the step S003, the melting temperature is between 580-640°C, and the melting operation is performed under an inert atmosphere.

5. The lanthanum-antimony-rare earth-added copper-zinc alloy according to claim 2, characterized in that: In step S004, the zinc-rare earth master alloy is cast into a volume between 40 cm 3 -80cm 3 Spherical.

6. The lanthanum-antimony-rare earth added copper-zinc alloy according to claim 1, characterized in that: The alloying additives include aluminum, iron, phosphorus, tin, indium and zirconium.

7. A method for preparing a lanthanum antimony rare earth added copper-zinc alloy, based on the lanthanum antimony rare earth added copper-zinc alloy as claimed in any one of claims 1 to 6, characterized in that: The steps include: S011, melting electrolytic copper, and adding alloy additives to the molten electrolytic copper to obtain an intermediate mixture; S012, adding zinc-rare earth master alloy to the intermediate mixture and continuing to stir until no bubbles are generated; S013. After refining and slag removal, casting is performed in a mold to obtain a rare earth copper-zinc alloy.

8. The method for preparing lanthanum, antimony and rare earth added copper-zinc alloy according to claim 7, characterized in that: In the step S011, the melting temperature of the electrolytic copper is between 1050-1150° C., and in the step S012, the mixing temperature is between 1000-1050° C., and the stirring rate is between 30-40 r / min.

Citation Information

Patent Citations

  • Copper alloy and preparation method and application thereof

    CN118256775A

  • Tin-brass alloy containing rare earth

    CN101157998A

  • Lead-free corrosion-resistant dezincification-resistant brass alloy and method for preparing same

    CN109266900A

  • Dezincification-resistant high-plasticity easy-to-machine H62 simple brass alloy and preparation method thereof

    CN112962002A

  • Copper alloy and its manufacturing method

    JP2005281714A